AI Technologies In The Accounting In The Post-COVID Era: A Survey of 231 Managers In Poland - Barbara GRABINSKA; Konrad GRABINSKI; Marcin KEDZIOR; Dorota KEDZIOR; Mariusz SOLTYSIK (Communications of International Proceedings, 2024)
The aim of the article is to determine factors influencing the adoption of AI technologies in the accounting area. The article presents the evolution of the accounting profession and the need to use information technology to a greater extent after the COVID pandemic. The study is based on the survey conducted among 231 managers from private, municipal and public entities in Poland. The article examines the impact of the institutional environment, accountants' experience, their competencies in the field of information technology, education, and openness to changes in the use of AI. The analysis of the empirical material was carried out using logistic regression with the odds ratio.